Phytochemical screening and antidyslipidemic effect of lime fruit (Citrus aurantifolia) ethanol extract on high-density lipoprotein levels of high-fat diet-induced rats - D M Putri, Nabila; Sovia, Evi; Iriawan, Jusron (ACTA Medical Health Sciences, 2025)
Dyslipidemia is a significant health problem in Indonesia and a major cause of coronary heart disease (CHD). According to the 2018 Riset Kesehatan Dasar Nasional (RISKESDAS), 24.3% of Indonesians aged ≥15 years had low high-density lipoprotein (HDL) levels, while 13.8% had high HDL levels. Treatment with traditional medicine is a popular approach in Indonesia. Lime (Citrus aurantifolia) contains flavonoids that can inhibit the activity of the hydroxymethylglutaryl-coenzyme A reductase (HMG-CoA reductase) enzyme. This study aimed to identify the chemical compounds found in lime peel and fruit, as well as to determine the effective dose of ethanol extract from lime fruit in increasing HDL levels. This research is a true experimental study conducted in the laboratory using an in vivo approach. The research used a randomized post-test only control group design involving both control and treatment groups. Based on the results of phytochemical screening, the lime fruit ethanol extract contains flavonoids, alkaloids, tannins, polyphenols, saponins, and quinones. Using the Saphiro-Wilk normality test, the data obtained are normally distributed with a p-value of 0.809 (p > 0.05). Statistical analysis was continued with the one-way ANOVA parametric test, and a p-value of 0.146 (p > 0.05) was obtained. An increase in the average HDL levels was also observed in the treatment group given a dose of 0.875 g/KgBW of lime fruit ethanol extract, but there was no significant difference in the average HDL levels between the groups. DOI : 10.35990/amhs.v3n3.p130-140 REFERENCES Agung LR. Pengaruh Daun Salam (Syzygium polyanthum) terhadap Kadar Trigliserida dan Kolesterol Total Darah pada Penderita Dislipidemia. J Ilm Kesehat Sandi Husada. 2021;10(2):408–12. Siregar SRM, Boy E. Faktor Risiko pada Pasien Dislipidemia. J Implementa Husada. 2022;3(4):230. Pengelolaan Dislipidemia di Indonesia 2021. PB Perkeni; 2021. p. 1–2. Gayatri AMT, Aulia AP, Riza M. Pengaruh Pemberian Ekstrak Biji Almond terhadap Kadar HDL. Studi Eksperimental pada Tikus Putih yang Diinduksi Kuning Telur. J Ilm Sultan Agung. 2023:889–97. https://jurnal.unissula.ac.id/index.php/JIMU/article/view/31396/84465 Rafsanjani MS, Asriati A, Kholidha AN, Alifariki LO. Hubungan Kadar High Density Lipoprotein (HDL) dengan Kejadian Hipertensi. J Profesi Med J Kedokt dan Kesehat. 2019;13(2):74–81. Badan Penelitian dan Pengembangan Kesehatan RI. Laporan Riskesdas 2018 Nasional. Lembaga Penerbit Balitbangkes; 2018. p. 156. Badan Penelitian dan Pengembangan Kesehatan RI. Laporan Riskesdas 2013 Nasional. Lembaga Penerbit Balitbangkes; 2013;127(3309):1275–9. Sinaga YO, Tiho M, Mewo YM. Gambaran Kadar Kolesterol High Density Lipoprotein Darah pada Mahasiswa Angkatan 2011 Fakultas Kedokteran Universitas Sam Ratulangi dengan Indeks Massa Tubuh ≥23,0 kg/m². J e-Biomedik. 2013;1(3):1096–100. Saragih AD. Terapi Dislipidemia untuk Mencegah Risiko Penyakit Jantung Koroner. Indones J Nurs Heal Sci. 2020;1(1):15–24. Panduan Tata Laksana Dislipidemia 2022. PB Perki; 2022. p. 128. Latif WD, Aswad M, Bahar MA. Perbandingan Efektivitas Klinik Simvastatin dan Atorvastatin terhadap Profil Lipid Darah: Studi Kasus di Rumah Sakit Universitas Hasanuddin. J Sains Farm Klin. 2022;9(1):34–41. doi:10.25077/jsfk.9.1.34-41.2022 Cyndi B, Andriane Y, Nur I. Pengaruh Pemberian Ekstrak Etanol Daun Jeruk Nipis (Citrus aurantifolia Swingle) terhadap Penurunan Kadar Kolesterol Total Darah pada Mencit Model Hiperkolesterolemia. Pros Pendidik Dr. 2016;2(2):911–8. Novriyanti R, Putri NEK, Rijai L. Skrining Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Etanol Kulit Jeruk Nipis (Citrus aurantifolia) Menggunakan Metode DPPH. Proceeding Mulawarman Pharm Conf. 2022;15:165–70. Mahmudi Y, Afrian S. Efektivitas Konsentrasi Ekstrak Kulit Jeruk Nipis (Citrus aurantifolia) dalam Menghambat Pertumbuhan Colletotrichum gloesporioides. J Agrotek Trop. 2021;10(2):85–93. Carvalho BMR, Nascimento LC, Nascimento JC, et al. Citrus Extract as a Perspective for the Control of Dyslipidemia: A Systematic Review With Meta-Analysis From Animal Models to Human Studies. Front Pharmacol. 2022;13(February):1–21. Pangestuti D. Pengaruh Pemberian Air Perasan Jeruk Nipis (Citrus aurantifolia Swingle) terhadap Kadar Kolesterol pada Mencit Hiperkolesterolemia. J Ris Hesti Medan. 2019;4(1):42–7. Mende R, Simbala H, Mansauda KLR. Uji Efektivitas Sari Buah dan Ekstrak Etanol Kulit Jeruk Nipis (Citrus aurantifolia) terhadap Hiperkolesterolemia pada Tikus Putih Jantan Galur Wistar (Rattus norvegicus). Pharmacon. 2021;10(1):676. Kemit N, Widarta IWR, Nocianitri KA. Pengaruh Jenis Pelarut dan Waktu Maserasi terhadap Kandungan Senyawa Flavonoid dan Aktivitas Antioksidan Ekstrak Daun Alpukat (Persea americana Mill). J Ilmu Teknol Pangan. 2016;5(2):130–41. Alaydrus S, Amara Pagal RP. Uji Efektivitas Ekstrak Etanol Biji Alpukat (Persea americana Mill.) terhadap Penurunan Kadar Kolesterol Total Tikus Putih Jantan Model Hiperkolesterolemia Diabetes. J Sains Kes. 2020;2(4):2407–6082. Untari MK, Pramukantoro GE. Aktivitas Antihiperkolesterolemia Ekstrak Etanol Daun Stevia Rebaudiana Bertoni pada Tikus Putih Jantan. J Syifa Sci Clin Res. 2020;2(1):11–20. Allain CC, Poon LS, Chan CSG, Richmond W, Fu PC. Enzymatic determination of total serum cholesterol. Clin Chem. 1974;20(4):470–5. Shchérazade OSF, Pétronille AZ, Joseph FKY, Georges A. Study of the Analgesic Effect of the Aqueous Extract of the Leaves of Citrus aurantifolia (Rutaceae) in Mice. GSC Biol Pharm Sci. 2021;14(3):207–14. Bawekes SM, Yudistira A, Rumondor EM. Uji Kualitatif Kandungan Senyawa Kimia Perasan Jeruk Nipis (Citrus aurantifolia Swingle). Pharmacon. 2023;12(3):373–7. Mazara F, Mahata LE, Kadri H, Putri BO. Efek Ekstrak Daun Kemangi (Ocimum basilicum L.) terhadap Kadar HDL Tikus Model Aterosklerosis. Jurnal XYZ. 2024;17(2). Chriscensia E, Wibowo EC, Enriko G, Wijaya OC. Phytochemical Screening, Therapeutic Benefits, and Adverse Effects of Citrus aurantifolia – A Review. J XYZ. 2020;2(2). Nisa IK, Amananti W, Febriyanti R. Skrining Fitokimia pada Kulit Jeruk Nipis di Wilayah Tegal dan Pemalang. 2021. Lin L-Y, Chuang C-H, Chen H-C. Lime (Citrus aurantifolia (Christm.) Swingle) Essential Oils: Volatile Compounds, Antioxidant Capacity, and Hypolipidemic Effect. Foods. 2019;8(398):1–11. Mustiqawati E, Yolandari S. Identifikasi Senyawa Saponin Ekstrak Daun Jeruk Nipis (Citrus aurantifolia S.) dengan Kromatografi Lapis Tipis. J Promot Prefentif. 2022;5(2):66–73. Afrina, Chismirina S, Magistra RY. Konsentrasi Hambat dan Bunuh Minimum Ekstrak Daun Jeruk Nipis (Citrus aurantifolia) terhadap Aggregatibacter actinomycetemcomitans secara In Vitro. Cakradonya Dent J. 2016;8(1):68–76. Ezeabara CA, Okeke C, Aziagba BO. Flavonoid Content of Citrus Species Grown in Awka, Anambra State, Southeastern Nigeria. Int J Agric Biosci. 2013;8(2):89–98. Mulyadi IC, Ratnawati H, Rosnaeni. Efek Ekstrak Etanol Daun Salam (Syzygium polyanthum (Wight) Walp) dibandingkan Simvastatin terhadap Kadar HDL Serum Tikus Wistar Jantan yang Diinduksi Pakan Tinggi Lemak. 2015:6. Depari SAF, Rambe DJA, Meilando R, et al. Uji Efektivitas Ekstrak Etanol Kulit Jeruk Sunkist (Citrus sinensis (L.) Osbeck) terhadap Kadar Kolesterol. J XYZ.